Assessing deceleration performance: methodological and practical considerations - Harper, D. J.; Philipp, N. M.; Eriksrud, O.; Jones, P. A.; Graham-Smith, P.; Dos`Santos, T. (Sports Medicine, 2026)
Deceleration is a critical locomotor skill for athletes competing in multi-directional speed sports. Greater deceleration can help athletes perform rapid reductions in velocity facilitating rapid changes of direction, whilst the high mechanical forces associated with braking can be linked to a heightened risk of fatigue, tissue damage and injuries. Despite the clear importance of deceleration in sport, research and applied practices in the past have predominantly focused on assessing an athlete`s sprint acceleration and maximum velocity capabilities, neglecting the necessity to be able to decelerate. With tactical evolutions in sports demanding athletes to accelerate and attain higher sprinting speeds more frequently in competition, there is increased necessity to decelerate and to be able to accurately assess this movement skill. Therefore, the aim of this article is to discuss methodological and practical considerations of the protocols and measurement technologies that can be used to assess deceleration in an applied field-based environment. The article highlights a range of different protocols (i.e. change of direction and acceleration-deceleration ability tests) and measurement technologies (i.e. radar, laser, video, global navigation satellite systems, inertial measurement units and motorised resistance devices) that can be used to evaluate deceleration and some of the advantages and disadvantages of each. Key metrics used to measure deceleration performance, and the kinematics underpinning deceleration technique are highlighted. Given the performance, health and injury-risk implications associated with deceleration, assessment of this movement skill should be given high priority within any athlete multi-disciplinary support system.